Measurements of pulse modulation in an ECM - Ronald, K; Cross, A; Phelps, A; He, W; Whyte, C; Thomson, J; Rafferty, E; Konoplev, I (2004)
We report on experiments which have recently been conducted at the University of Strathclyde investigating rapid amplitude modulations occurring in the microwave output radiation of an electron cyclotron maser (ECM). The experiment used an electron beam injected from a co-axial diode with knife-edged graphite cathode in the fringing field of an adjustable magnet system producing a beam of up to 175kV and 140A. The time evolution of the electron beam was measured as the cathode plasma expanded using a Faraday cup in conjunction with upstream beam interceptors as a function of the magnetic compression ratio. The ECM cavity was configured so that its length and the length of the interaction space could be readily adjusted. The microwave output signal was studied using special fast rectifying diode detectors, a high performance deep memory oscilloscope and cut-off filters. Steady-state output was observed at high magnetic compression ratios (16:1) at a frequency of 16GHz corresponding to cyclotron resonant maser (CRM) coupling between the beam and the radiation in the expected TE1,2 mode. At lower compression ratios modulation was observed after an initial steady-state period and shown by antenna pattern measurements to be associated with transverse mode competition in the microwave cavity. © 2004 Elsevier B.V. All rights reserved.